Public cardiopulmonary resuscitation training rates and awareness of hands-only cardiopulmonary resuscitation: A cross-sectional survey of Victorians - Bray, Janet; Smith, K.; Case, R.; Cartledge, S.; Straney, L.; Finn, J. (2017)
© 2017 Australasian College for Emergency Medicine & Australasian Society for Emergency Medicine.Objectives: To provide contemporary Australian data on the public's training in cardiopulmonary resuscitation (CPR) and awareness of hands-only CPR. Methods: A cross-sectional telephone survey in April 2016 of adult residents of the Australian state of Victoria was conducted. Primary outcomes were rates of CPR training and awareness of hands-only CPR. Results: Of the 404 adults surveyed (mean age 55 ± 17 years, 59% female, 73% metropolitan residents), 274 (68%) had undergone CPR training. Only 50% (n = 201) had heard of hands-only CPR, with most citing first-aid courses (41%) and media (36%) as sources of information. Of those who had undergone training, the majority had received training more than 5 years previously (52%) and only 28% had received training or refreshed training in the past 12 months. Most received training in a formal first-aid class (43%), and received training as a requirement for work (67%). The most common reasons for not having training were: they had never thought about it (59%), did not have time (25%) and did not know where to learn (15%). Compared to standard CPR, a greater proportion of respondents were willing to provide hands-only CPR for strangers (67% vs 86%, P < 0.001). Conclusion: From an Australian perspective, there is still room for improvement in CPR training rates and awareness of hands-only CPR. Further promotion of hands-only CPR and self-instruction (e.g. DVD kits or online) may see further improvements in CPR training and bystander CPR rates.